Synaptic Dysfunction in Alzheimer’s Disease and Glaucoma: From Common Degenerative Mechanisms Toward Neuroprotection - Criscuolo, Chiara; Fabiani, Carlotta; Cerri, Elisa; Domenici, Luciano (Frontiers in Cellular Neuroscience, 2017)
Alzheimer’s disease and glaucoma are two distinct multifactorial neurodegenerative diseases, primarily affecting the elderly. Common pathophysiological mechanisms have been elucidated in the past decades. First of all both diseases are progressive, with Alzheimer’s disease leading to dementia and glaucoma inducing blindness. Pathologically, they all feature synaptic dysfunction with changes of neuronal circuitry, progressive accumulation of protein aggregates such as the beta amyloid and intracellular microtubule inclusions containing hyperphosphorylated tau, which belongs to microtubule associated protein family. During an early phase of degeneration, both diseases are characterized by synaptic dysfunction and changes of mitogen-activated protein kinases (MAPK). Common mechanisms underlying both diseases are discussed here, along with recent results on the potential use of the visual system as a biomarker for diagnosis and progression of Alzheimer’s disease. Common neuropathological changes and mechanisms in Alzheimer’s disease and glaucoma have facilitated the transfer of therapeutic strategies between diseases. In particular, we discuss past and present evidence for neuroprotective effects of brain-derived neurotrophic factor.